2018
DOI: 10.29252/jrh.8.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spiritual family therapy on marital satisfaction in couples with husbands' drug-dependent

Abstract: Addiction and Problematic drug use, led to the physical, psychological, social and family destruction especially clinically significant or serious discomfort. This study aimed to efficacy of spiritual therapy based on family-centered on marriage satisfaction in couples with husbands' drug-dependent. This design was a quasi-experimental. The population consisted all drug-dependent and their wives in Quchan (prisoners and patients referred to the clinics withdrawal). 40 couples volunteered to participate in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Married individuals with high spiritual well-being tend to have higher satisfaction in marriage compared to those with low spiritual well-being. The findings of this study are in line with previous studies in this area (Aman, Abbas, Nurunnabi & Bano, 2019;Kasapoğlu, &Yabanigül, 2018 andHernandez-Kane, &Mahoney, 2018;Khurana & Joshi, 2017;Beyranvand, Azizi, &Dehghan Manshadi, 2016 andKhakpour, Mehrafarid, Akbari Amarghan, Nejat, Fazayeli Yousefabad, &Toroghi, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Married individuals with high spiritual well-being tend to have higher satisfaction in marriage compared to those with low spiritual well-being. The findings of this study are in line with previous studies in this area (Aman, Abbas, Nurunnabi & Bano, 2019;Kasapoğlu, &Yabanigül, 2018 andHernandez-Kane, &Mahoney, 2018;Khurana & Joshi, 2017;Beyranvand, Azizi, &Dehghan Manshadi, 2016 andKhakpour, Mehrafarid, Akbari Amarghan, Nejat, Fazayeli Yousefabad, &Toroghi, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Since Spiritually-Oriented Cognitive-Behavioral Family Therapy has only recently been included among the categories of family therapy types in Cognitive-Behavioral Family Therapy, there are only a limited number of studies in the literature on it. Even if few in number, Khodayarifard and McClenon (2011), Khakpour et al (2018), Smith and Smith (2004), Prest and Robinson (2006), and Khodayarifard and Fatemi (2013) have conducted diverse studies on spiritually-oriented CBFT.…”
Section: Discussionmentioning
confidence: 99%
“…Summary, conclusions reached, and program evaluation with both partners (e.g., opinions of the program, strong and weak points). Khakpour et al (2018) found that after 10 sessions of CBT-based spiritual family therapy with couples, both partners' marriage satisfaction, positive thoughts, problem-solving skills, personal behaviors, emotions, and religious orientations significantly improved.…”
Section: Spiritual-based Applications In Cognitive-behavioral Family Therapymentioning
confidence: 96%
See 2 more Smart Citations